Been soursop Extract Against Larvae of Aedes sp Killing Activity - Nurul Inayati; Maruni Wiwin Diarti; Erlin Yustin Tatontos (Poltekkes Kemenkes Semarang, 2013)
The aim of this studyis to determine thedose of been soursop extract against larvae of Aedes sp killing activity (larvacida) that derived from dengue endemic are asin Mataram with bioas say testingin the laboratory.The research methodused wascompletely randomized experimental design. The samples used wereinstar III oflarvaeAedesspderived from eggsof Aedes sp mosquitoes that were collectedin the homes of residentsin endemic areas dengue feverin the city of Mataram.Results of bioas say testin the laboratory was obtained D56 and LD90 are 0.14 ppm and 0.20 ppm respectively. So that, the been of soursop extract is effective tokill the larvaeof Aedes sp.